SCREENING OF INSECTICIDAL POTENTIALS OF TWENTY (20) BOTANICAL PLANT POWDERS LOCALLY ACCESSIBLE FOR THE PROTECTION OF STORED LENTIL SEEDS (LENS CULINARIS) AGAINST INFESTATION OF CALLOSOBRUCHUS MACULATUS IN MAIDUGURI - Bukar, A.; Zubairu, M.; Kumshe, I. B.; Dawud, A. M. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The insecticidal potential of 20 botanical powders against cowpea weevil (Callosobruchus maculatus (F.) (Coleoptera: Chrysomelidae) on stored lentil was evaluated. The powders of Vernonia ambigua, Momordica charantica, Euphorbia hirta, Mentha arvensis, Cassia tora, Mitracarpus spp, Laportea canadensis, Amaranthus spinonsus, Tridax procumbens, Ocimum basilicum, Origanum vulgare, Thymus vulgaris, Senna occidentalis, Syzgium aromaticum, Nigella sativa, Piper nigrum, Zingiber officinale, Coriandrum sativum, Allium sativum, Myristica fragrans and Capsicum annum were used throughout the experiment. Data were recorded on adult mortality after 24, 48, 72 hours of exposure and oviposition, progeny emergence, weight loss, damage and germination potentials after 100 days of treatments. The rate of 500 mg/kg botanical powders were applied to lentil seeds infested with C. maculatus (F.). The result revealed that, highest number of mortality, oviposition, progeny emergence, weight loss and germination potential were observed with the application of C. sativum, Z. officinale, P. nigrum, E. hirta, T. procumbens, S. aromaticum, A. sativum, T. vulgaris, C. tora, A. spinonsus, M. spp, M. charantica, M. avensis, S. occidentalis, N. sativa, V. ambiqua, M. frangrans, O. basilicum, L. canadensis and O. vulgare on lentil seed, while minimum number was recorded under control. The insecticidal activity of these powders was in the order of C. sativum> Z. officinale> P. nigrum> E. hirta> T. procumbens> S. aromaticum> A. sativum> T. vulgaris> C. tora> A. spinonsus> M. spp> M. charantica> M. avensis> S. occidentalis> N. sativa> V. ambiqua> M. frangrans> O. basilicum> L. Canadensis>and O. vulgare> showed high potential protection of lentils seeds against C. maculatus infestation and germination of the treated seeds after 100 days of storage.